Ceramic Traditions and Cultural Identities: West‐Central France during the Late Neolithic II Period (c.3400–2900 cal. BC). Issue 4 (10th October 2013) - Ard, Vincent
Summary Pottery is generally used as the main basis for characterizing Neolithic cultural identities: archaeologists tend to define groups and cultures in time and space on the basis of typological classification. This paper proposes a different approach to the study of pottery that takes into account the various steps of the chaîne opératoire of manufacture, particularly the methods used to form and finish the pots, in order to characterize the cultural landscape of the Late Neolithic II period in west‐central France (3400−2900 BC). This cultural landscape has hitherto been poorly defined and subject to endless debate since the 1950s, largely because the pottery is fairly homogeneous in shape and is mostly undecorated. The technological study presented here, based on the examination of 23 ceramic assemblages and focusing on a variety of stages in the chaîne opératoire, has allowed the definition of three technical traditions. The main characteristics and diagnostic features of these traditions are outlined below, together with their interrelationships.